Study on Social Security and Social Transplantation - Cantarovich, Félix (Highlights on Medicine and Medical Research Vol. 4, 2021)
The primary intention of this study is to discuss about a current social health and economic crisis, generated by the privileged advance of medical sciences. The success in medical action against diseases, plus the progress in population life survival, has conditioned a progressive increase of patients with the so called ‘End stage organ failure’, terminal phase of organic systems indispensable for life. In parallel scientific research and medical engineering, has achieved a significant development of the substitution of vital organs, particularly in the case of extracorporeal dialysis, and as well, by the vertiginous advance of organ transplantation. These positive solutions have conditioned a global and urgent social problem: People’s insufficient organ donation. Significantly linked with this crisis of public health, globally economic resources and the real possibilities of people’s assistance by social security, have been seriously compromised by the high cost of haemodialysis and as well, by the inexorably annual increase of patients requiring transplantation to stay alive. The main alternatives to solve this complex socioeconomic crisis tending to unbalance Social Security institution response to the needs of the people, are prevention of end-stage organ failure and also an updated of social and university education about transplantation and organ donation